Practice and Perception of Radiographers on the Positioning Techniques of Erect Lateral Cervical Spine Radiography in Non-trauma Adult Patients - B.S. Weerakoon; I.G.N.N.K. Karunaratne; .M.W.S. Jayasundara (Sudan Journal of Medical Sciences)
Background: The visualization of the lower cervical spine (C-spine), including the C7-T1 junction on lateral radiograph is a challenge due to the overlapping of the shoulder girdle. Therefore, the radiographers have adapted different positioning strategies to overcome this challenge. This study explores the current practice and perception of radiographers on positioning techniques of erect lateral cervical spine radiography in non-trauma adult patients.